ANATOMY OF CASSAVA LEAVES - de Oliveira, Eli Carlos; Miglioranza, Édison (European Scientific Journal, ESJ, 2014)
Leaves are the organs in which occurs mainly photosynthesis enabling the transformation of radiant energy into chemical energy. Anatomical properties in leaves are indices used in taxonomical studies the importance of anatomical features on the studies support morphological evidence for separating taxa of plants Manihot at the generic level. The present study is aiming to introduce an internal description of leaves of cassava plants to determine its characteristics and thus contribute to other research that may need this description. The observation was surface replicas of the leaf made from transparent materials and scanning electron microscopy (SEM) were compared for their ability to present an accurate picture of the leaf. According to the observations, we can infer that, cassava is presented as a very rustic plant by adapting to different environments. The completion of the anatomical study of leaf Manihot esculenta IAC 576-70, showed that the sheet, the body responsible the synthesis of carbohydrates and chief of tuberization root has important morpho-anatomical features, such as presence papillae on the abaxial epidermis by increasing the surface forming a crown around the stomata, thereby contributing to the same remain open for longer in areas with water deficit.